Why internet users' perceptions of viewing child exploitation material matter for prevention policies. Issue 2 (June 2020) - Hunn, Charlotte; Spiranovic, Caroline; Prichard, Jeremy; Gelb, Karen
There are claims that the societal appetite for 'child exploitation material' is increasing. Yet, Australia's policy response does not include initiatives to dissuade potential offenders from deliberately viewing child exploitation material for the first time (onset). To critically examine this issue, this paper draws on Situational Crime Prevention theory. It argues that (a) many first-time child exploitation material viewers fit the Situational Crime Prevention construct of the Opportunistic Offender and (b) suggests that current policy overlooks the kinds of non-instrumental factors that increase the risk of onset for this group, including doubts about the criminality and harmfulness of viewing child exploitation material. The paper then empirically examines social attitudes to child exploitation material viewing by presenting the findings of a survey of 504 Australian internet users. Results indicate that a sizeable minority of the participants were: unaware that it is a crime to view certain types of child exploitation material in Australia; and held doubts about the harmfulness of viewing child exploitation material. These findings are used to reflect on how the presence of these non-instrumental factors among ordinary internet users may affect the offending readiness of the Opportunistic Offender. Policy implications are then briefly discussed.